Fluid management in ARDS: an evaluation of current practice and the association between early diuretic use and hospital mortality - Seitz, Kevin P. (J Intensive Care, 2020)
BACKGROUND: Acute respiratory distress syndrome (ARDS) and volume overload are associated with increased hospital mortality. Evidence supports conservative fluid management in ARDS, but whether current practice reflects the implementation of that evidence has not been described. This study reports the variability in contemporary fluid management for ICU patients with ARDS. We compared routine care to trial protocols and analyzed whether more conservative management with diuretic medications in contemporary, usual care is associated with outcomes. METHODS: We performed a retrospective cohort study in nine ICUs at two academic hospitals during 2016 and 2017. We included 234 adult patients with ARDS in an ICU at least 3 days after meeting moderate-severe ARDS criteria (PaO(2):FIO(2) ≤ 150). The primary exposure was any diuretic use in 48 to 72 h after meeting ARDS criteria. The primary outcome was hospital mortality. Unadjusted statistical analyses and multivariable logistic regression were used. RESULTS: In 48–72 h after meeting ARDS criteria, 116 patients (50%) received a diuretic. In-hospital mortality was lower in the group that received diuretics than in the group that did not (14% vs 25%; p = 0.025). At ARDS onset, both groups had similar Sequential Organ Failure Assessment scores and ICU fluid balances. During the first 48 h after ARDS, the diuretic group received less crystalloid fluid than the no diuretic group (median [inter-quartile range]: 1.2 L [0.2–2.8] vs 2.4 L [1.2-5.0]; p < 0.001), but both groups received more fluid from medications and nutrition than from crystalloid. At 48 h, the prevalence of volume overload (ICU fluid balance >10% of body weight) in each group was 16% and 25%(p = 0.09), respectively. During 48–72 h after ARDS, the overall prevalence of shock was 44% and similar across both groups. Central venous pressure was recorded in only 18% of patients. Adjusting for confounders, early diuretic use was independently associated with lower hospital mortality (AOR 0.46, 95%CI [0.22, 0.96]). CONCLUSIONS: In this sample of ARDS patients, volume overload was common, and early diuretic use was independently associated with lower hospital mortality. These findings support the importance of fluid management in ARDS and suggest opportunities for further study and implementation of conservative fluid strategies into usual care.